2005
DOI: 10.1021/la047338h
|View full text |Cite
|
Sign up to set email alerts
|

First Reaction of a Bare Silicon Surface with Acid Chlorides and a One-Step Preparation of Acid Chloride Terminated Monolayers on Scribed Silicon

Abstract: Methyl-terminated and acyl chloride terminated monolayers are produced when silicon is scribed under mono- and diacid chlorides, respectively. To the best of our knowledge, this is the first report of the reaction between a bare silicon surface and acid chlorides. This reaction takes place by wetting the silicon surface in the air with the acid chloride and scribing. Scribing activates the silicon surface by removing its passivation layer. We propose that scribed silicon abstracts chlorine from an acid chlorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 34 publications
4
40
0
Order By: Relevance
“…[442]. c 2007, American Chemical Society studies supported the assumptions made based on the experimental investigation [450]. Finally, the most recent work on scribed silicon surface modification using 1,9-decadiene suggested that the majority of reactions of this compound proceeds via addition of only one alkene group leaving the other to be available for further modification, as was supported by chemical verification with bromine, osmium tetroxide, dichlorocarbene, and ((cyclohexyl) 3 P) 2 Cl 2 Ru=CHPh (Grubbs' catalyst) [452].…”
Section: Chemistry Of Scribed Siliconmentioning
confidence: 64%
See 3 more Smart Citations
“…[442]. c 2007, American Chemical Society studies supported the assumptions made based on the experimental investigation [450]. Finally, the most recent work on scribed silicon surface modification using 1,9-decadiene suggested that the majority of reactions of this compound proceeds via addition of only one alkene group leaving the other to be available for further modification, as was supported by chemical verification with bromine, osmium tetroxide, dichlorocarbene, and ((cyclohexyl) 3 P) 2 Cl 2 Ru=CHPh (Grubbs' catalyst) [452].…”
Section: Chemistry Of Scribed Siliconmentioning
confidence: 64%
“…The 1-alkenes [443][444][445], 1-alkynes [443,445], aldehydes [446], alcohols [444], alkyl halides [445,447,448], epoxides [449], and acid chlorides [450] all react with the scribed silicon surface in a manner similar to that expected for Si (100) and Si(111) substrates. According to the review [442], the examples of epoxides [449] and acid chlorides [450] were the first demonstration of the reactivity of this type of compounds with bare silicon. For the types of surface reactive sites available on Si(100) and Si (111) surfaces, the products of selected reactions are listed in Fig.…”
Section: Chemistry Of Scribed Siliconmentioning
confidence: 80%
See 2 more Smart Citations
“…Hussani et al reported a photochemical means of forming acyl chloride terminated silicon surfaces by adding gaseous oxalyl chloride to an evacuated quartz cell containing an alkyl-modified Si(111) surface and irradiating with 367nm light 16. Lua et al modified silicon surfaces with suberoyl chloride under dry conditions, in which one of the acyl chlorides reacted with the silicon surface while the second acyl chloride was reacted with amine-containing molecules 17. Duevel, et al have also fabricated acyl chloride-modified gold SAMs 18…”
Section: Introductionmentioning
confidence: 99%